A new genus of the subfamily Cillaeinae (Coleoptera, Nitidulidae) from the Philippines and New Guinea with notes on the taxonomy and phylogeny of the subfamily - Kirejtshuk, Alexander G.; Kovalev, Alexey V. (Zootaxa, 2016)
Allenipeplus gen. nov. represented by A. philippinensis sp. nov., type species (Philippines, Luzon), A. alius sp. nov. (Philippines, Mindoro), A. harmonicus sp. nov. (Philippines, Mindanao) and A. vitellinus sp. nov. (Indonesian New Guinea), is described. This new genus combines characters with a mosaic spread among other cillaeine genera. We present a wide comparison of genera among the subfamily Cillaeinae, making it possible to elaborate a detailed diagnosis of the new genus and trace some order in character patterns and propose a hypothesis on the relationship of this genus to other groups known from the Indo-Malayan and Australian Regions. A detailed diagnosis of the new genus and key to the new species are given. The Adocimus-complex of the related genera including Allenipeplus gen. nov., Adocimus Murray, 1864, Ithyphenes Murray, 1864, Platynema Ritsema, 1885 and probably Brittonema Kirejtshuk, 2011 is defined. Some notes on the taxonomy of the genera Liparopeplus Murray, 1864 and Xanthopeplus Fairmaire, 1880, stat. nov. are given. Additionally, designation of a lectotype for Liparopeplus colastoides Murray, 1864 is made.